PENERAPAN KONSEP WELFARE STATE DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI INDONESIA - Sindi Fitria; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2021)
The concept of Welfare State prioritizes the implementation of community welfare which can be provided through good public services, where it is the right and expectation of every citizen. To construct good public services, the elements that must be fulfilled, such as the element of openness, supervision and justice. Therefore, the state has a role in managing the economy which includes the responsibility to ensure the unity of basic welfare services to a certain level.For that, the state needs cooperative contribution between the government and the society to create good public services. The concept of public services in Indonesia regulated in the Law of Republic Indonesia No. 25 of 2009 concerning Public Services hasn't shown a sufficiently ideal implementation. In fact, the public always demands the best quality service in accordance with what has been determined, especially from government officials, both private as well as others. Even though the results aren't in accordance with their expectations because the publicservices shown thus far seem slow, convoluted, expensive, and exhausting. Therefore, the duty of the state, especially public service providers, is obliged to build public trust in public services in line with the hopes and demands of all citizens and residents in Indonesia.